Peran platform digital dalam pemasaran kue pukis - Putra, Ryan Eka (Maliki Interdisciplinary Journal, 2025)
Digital platforms have transformed the marketing of pukis cakes by making it easier for MSMEs to reach a wider market without relying on physical locations. Data-driven promotional features, digital payment systems, and delivery services increase visibility, transaction efficiency, and customer satisfaction. Challenges such as internet dependence and intense competition must be overcome through creative content and strategic collaboration. However, opportunities such as local food trends and government support offer hope for the growth of this business. This study emphasizes how digital transformation is key to the competitiveness of traditional culinary MSMEs in the digital economy era. Therefore, utilizing digital platforms is not merely a marketing tool but also an adaptive strategy that enables pukis cake MSMEs to survive, thrive, and build a relevant brand identity amidst changing consumer behavior and fast-paced market dynamics.